Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian (Studi pada Two Way Cake Pixy di Tiktok Shop) - Anjarsari, Dyah; Rahmi, Palupi Permata (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to determine the effect of Online Customer Review and Online Customer Rating on customer decisions on Two way cake Pixy products at Tiktok Shop. The research method used is descriptive and verification method with a quantitative approach. The sampling technique used in the study used probability sampling with a simple random sampling technique with a total research population of 100 respondents determined using the Slovin formula. The analysis used includes validity test, reliability test, classical assumption test, multiple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. Descriptive purchasing decisions are rated as disagree, Online Customer Review is rated as strongly agree and Online Customer Rating is rated as strongly agree. The results of the coefficient of determination show that the contribution of Online Customer Review to Purchasing Decisions is 8,5% and the remaining 91,5% is influenced by other factors not examined. In addition, from the results of the study it can be seen that the variables Online Customer Review (X1) and Online Customer Rating (X2) have a partial effect on Customer Decisions (Y). Simultaneously, the variables Online Customer Review (X1), and Online Customer Rating (X2) have an effect on Customer Decisions (Y).